Sistem Kendali Navigasi Wahana Selam AUV Menggunakan Jaringan GSM - Udink Aulia; Muhammad Tadjuddin (Jurnal Teknik Mesin Unsyiah, 2013)
Indonesian ocean has a riches of maritime ​​fishery potency, so fishery mapping is important to be maintained, examined and explored. Fishery potency observation requires a vehicle to bring the observations and data collection equipments to the seabed by an electric-powered underwater vehicle or AUV (Autonomous Underwater Vehicle). AUV is a kind of underwater vehicle that has an ability to bring underwater observation’s instrument. The operation of these vehicles is wireless and autonomous. It is able to move to specific locations in accordance with trajectory in the programmable microcontroller and the GPS sensors. The aim this research is to design a control system for underwater survey that can make a communication to control center on the beach by sending and receiving SMS thru GSM network. This AUV communication systems to explore coastal area, moving from one point of observation to the next observation point (point to point) in accordance with the latitude and longitude that is programmed and customized using GIS MapQuest software, and also trajectory correction control system by using GPS. In this paper, we described control systems and data communication for navigating auv based on GPS, GSM and GIS technology. Development control systems includes trajectory monitoring system, long range control by GSM network and position tracking by GIS .